Nuclear Localization of the p75 Neurotrophin Receptor Intracellular Domain - Parkhurst, Christopher N. (American Society for Biochemistry and Molecular Biology, 2010)
The p75 neurotrophin receptor, a member of the tumor necrosis factor superfamily of receptors, undergoes an α-secretase-mediated release of its extracellular domain, followed by a γ-secretase-mediated intramembrane cleavage. Like amyloid precursor protein and Notch, γ-secretase cleavage of the p75 receptor releases an intracellular domain (ICD). However, it has been experimentally challenging to determine the precise subcellular localization and functional consequences of the p75 ICD. Here, we utilized a nuclear translocation assay and biochemical fractionation approaches to follow the fate of the ICD. We found that the p75 ICD can translocate to the nucleus to activate a green fluorescent protein reporter gene. Furthermore, the p75 ICD was localized in nuclear fractions. Chromatin immunoprecipitation experiments indicated that nerve growth factor induced the association of endogenous p75 with the cyclin E(1) promoter. Expression of the p75 ICD resulted in modulation of gene expression from this locus. These results suggest that the p75 ICD generated by γ-secretase cleavage is capable of modulating transcriptional events in the nucleus.